You should smile more : a novel - Ryan, Anastasia (Sourcebooks Casablanca, 2023)
"When Vanessa Blair is fired because of her "resting bitch face," her friends help her launch a revenge plan that'll bring down the whole company. Telemarketer Vanessa Blair isn't in love with her job. It pays the bills and feeds her foster kittens, but offers only one other perk: her friendships with Jane Delaney and Trisha Lam. But, as mind-numbing as her job is, things are about to get worse. Xavier Adams, her self-absorbed boss, calls Vanessa into the conference room and fires her. The reason? Her facial expressions. Apparently, her resting bitch face is wide awake, and it doesn't matter that her sales numbers are stellar or that she organizes office events. After a girls' night of schnapps and imagining retribution, Vanessa awakens to find that Trisha is more literal than she thought, and has implemented a revenge strategy based on the classic business book The Art of War by Sun Tzu. At first, Vanessa wants nothing to do with it. She wants to file for unemployment and move on with her life, possibly with Carter Beckett, the cute, cat-loving unemployment rep assigned to her case. But when Xavier contests her unemployment and ruins her shot at her dream job, Vanessa is all in..."--